(untitled) (Revista Espaço e Geografia, 2022)
Manmade fragmentation of the Brazilian Atlantic forest poses a serious threat to the biodiversity of the various ecosystems of this unique biome. To counteract this fragmentation process, the Serra dos Órgãos National Park initiated an expansion project aiming at the inclusion of the adjacent Serra da Estrela mountain range into the National Park area. This work analyzes this region from two different points of view to define the most suitable expansion possibility. The protection suitability evaluation assesses the individual landscape patches according to their ecological value. The urbanization suitability evaluation assesses the same landscape patches according to their suitability for future urban growth. To calculate the suitability for protection, as well as urbanization, the method of Multi-Criteria Evaluation (MCE) is applied. The results of the two suitability evaluations are combined and analyzed to identify core areas and conflict zones of the potential expansion area of the National Park.